Energy-Efficient Hybrid Hierarchical Routing scheme for overall Efficiency in WSN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless Sensor Network are spatially distributed sensors intended to monitor different physiological conditions. Sensing and communicating data from one place to another consumes more energy, therefore the management of sensor energy is a very important factor. Energy utilization, synchronization, and a lifetime of the network are the main criteria in WSN. More energy is utilized by sensors that are distant from the base station. The gateway nodes are deployed to collect and relay information from nodes to the base station to resolve this problem. To decrease energy consumption, gateway nodes are deployed in the network. In this paper, a hybrid approach is used to increase the overall efficiency of the network in WSNs with time synchronization which increases the throughput of the network. The efficiency of proposed protocol based network has shown improvements in network lifetime, residual energy, data packets, and the throughput of the network. The performance of WSN of the proposed scheme is compared to other classical routing schemes and the proposed algorithm has proved its merit.